MINERAL CHEMISTRY OF A ZIRCON-BEARING, COMPOSITE, VEINED AND METASOMATISED UPPER-MANTLE PERIDOTITE XENOLITH FROM KIMBERLITE - Dawson J.B.; Hill P.G.; Kinny P.D. (My University, 2001)
Zircon-bearing veins in a harzburgite xenolith from kimberlite have imposed Ca-metasomatism on the harzburgite wall rock, in addition to adding K, Fe, Ti and OH. The zircon, previously dated to have an age similar to that of the xenolith-hosting kimberlite, shows higher Y, Nb, Ba, REE, Th and U contents than other mantle-derived zircons. Peripheral alteration of the zircon to baddeleyite and zirconolite, and alteration of vein ilmenite to perovskite suggest reaction with an evolving carbonatitic kimberlite melt. The high Cr2O3 content (0.77 wt%) of the zirconolite extends the compositional range of terrestrial zirconolite.